1995
DOI: 10.1093/clinids/21.5.1308
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus as a Community Organism

Abstract: An increase in methicillin-resistant Staphylococcus aureus (MRSA) infections prompted a study of MRSA during a 21-month period in a 600-bed university hospital in southern Texas. MRSA cases were classified as community, nosocomial, or transfer cases. A case-control study of risk factors for community MRSA compared with community methicillin-susceptible S. aureus (MSSA) was performed. Pulsed field gel electrophoresis (PFGE) of whole cell DNA typing was used as a marker of strain identity for 31 consecutive isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
1
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(119 citation statements)
references
References 6 publications
3
113
1
2
Order By: Relevance
“…[12][13][14][15][16] More-recent reports have suggested that other risk factors also may exist, such as household contacts with risk factors for MRSA and child-care attendance. [17][18][19] Notably, the CA-MRSA isolates described in the past decade differ significantly from previous strains of MRSA in that they have distinct DNA-fingerprinting patterns 20 and lack multidrug resistance.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] More-recent reports have suggested that other risk factors also may exist, such as household contacts with risk factors for MRSA and child-care attendance. [17][18][19] Notably, the CA-MRSA isolates described in the past decade differ significantly from previous strains of MRSA in that they have distinct DNA-fingerprinting patterns 20 and lack multidrug resistance.…”
mentioning
confidence: 99%
“…12 Over the last decade, MRSA has become increasingly common in hospitals and in community settings. [22][23][24] Combination antimicrobial is an important treatment approach for infections. Synergy is one of the most common reasons for using combination antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Further information should be collected to develop a hypothesis on risk factors specific for community acquisition. Intravenous drug use, previous antibiotic use, and underlying diseases have previously been associated with community acquisition of MRSA (147,176). A recent study covering 30 months identified a similar proportion (22%, 20/92) of community-acquired MRSA in a university hospital.…”
Section: Mrsa In Communitymentioning
confidence: 93%